Epidemiology and clinical manifestations of SARS-CoV2 infection - Espinoza, Luis A. (2021)
Over the last year, the whole world has been affected by the COVID-19 pandemic, with over 80 million people affected with more than 1.8 million dead over the same period. Like other recent epidemics, this seems to be zoonotic in origin with the bats as the primary species harboring these coronaviruses but with a still unnamed intermediary host. Up to 80% of the cases have minor symptoms but 5% of the remainder may develop severe complications including respiratory failure. There has been a fast development of the knowledge about the disease in a very short period of time, making it a less lethal disease now as well as accelerating the development of several available vaccines.